ChemInform Abstract: Asymmetric Ruthenium‐Catalyzed Hydrogenation of 2‐ and 2, 9‐Substituted 1, 10‐Phenanthrolines. Issue 48 (26th November 2013) - Wang, Tianli; Chen, Fei; Qin, Jie; He, Yan‐Mei; Fan, Qing‐Hua
Abstract The first highly enantio‐ and diastereoselective hydrogenation of 2, 9‐ and 1, 10‐phenanthrolines using a chiral cationic ruthenium diamine catalyst is presented.